Opioid Use Disorder among Patients with Sickle Cell Disease at Usmanu Danfodiyo University Teaching Hospital Sokoto - Yakubu Ibrahim Anas; Musa Usman Umar; Tomori Abdulfatai Bakare; Sani Bako Abubakar; Ahmad Abubakar; Abubakar Mayana Usman; Abdulaziz Danmadami Mohammad; Jibril Abubakar; Ibrahim Yusuf (Nigerian Journal of Medicine)
Background: Opioid use is prevalent among sickle cell disease (SCD) patients due to recurrent painful vaso-occlusive crises, and repeated use is linked to a heightened propensity for opioid use disorder (OUD), significantly impacting their quality of life and increasing morbidity and mortality. Aim: The aim of the study was to determine the prevalence and determinants of OUD among patients with SCD. Methodology: The study was conducted at the Usmanu Danfodiyo University Teaching Hospital (UDUTH) in Sokoto, and it involved the use of self- and interviewer-administered questionnaires among SCD patients. Results: The prevalence of OUD was 11.7%, with 95% confidence interval (7.6, 16.8%). In addition, 5.3%, 3.4% and 1.0% of participants had mild, moderate and severe OUDs, respectively. OUD showed a significant association with insurance service users (P = 0.008) and higher pain scores (P = 0.036), but not with gender (P = 1.000), haemoglobin type (P = 1.000) or the steady state packed cell volume (P = 0.085). Conclusion: The prevalence of OUD is high among individuals with SCD. The use of insurance services and higher pain scores were identified as factors associated with OUD. There is a clear need to screen for non-medical use of opioids among patients with SCD.